2020
DOI: 10.1088/1757-899x/830/4/042002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of solid waste management through composting: A comparative study of rural communities in Malaysia and Indonesia

Abstract: Along with increasing human activity, the waste generated from these activities more and more. Waste at this time has become one of the causes of disasters in the world. One type of waste produced is organic waste. Organic waste is one of the solid wastes produced from domestic waste. Research is conducted to understand how people carry out organic waste processing into compost, to improve the quality of life, especially in economic terms. In addition, it can be identified factors and obstacles that affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…On the other hand, exposure to waste segregation through recycling has been widely spread among the population; however, the action on composting activities is still limited. According to [22], a small group of people practised composting while the others were unaware of the activities due to lack of information [22]. Therefore, the well-structured mechanisms of this awareness programme can be enhanced [14].…”
Section: Methods That Can Encourage Waste Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, exposure to waste segregation through recycling has been widely spread among the population; however, the action on composting activities is still limited. According to [22], a small group of people practised composting while the others were unaware of the activities due to lack of information [22]. Therefore, the well-structured mechanisms of this awareness programme can be enhanced [14].…”
Section: Methods That Can Encourage Waste Segregationmentioning
confidence: 99%
“…However, only a small portion is practising composting in their home, 27% in suburban and 24% in urban areas. Minimal participation in composting revealed that 60% of citizens consider composting not beneficial and a dirty job [22]. [23]The composting plants have been increasing worldwide, whereas, in Europe, less biodegradable waste has been brought to the landfill following the directive's policy and penalties along with high disposal costs [24].…”
Section: The Level Of Knowledge and Awareness On Recycling And Compos...mentioning
confidence: 99%